Post-transcriptional and Post-translational Modifications of Primary Cilia: How to Fine Tune Your Neuronal Antenna - Rocha, Cecilia; Prinos, Panagiotis (Frontiers in Cellular Neuroscience, 2022)
Primary cilia direct cellular signalling events during brain development and neuronal differentiation. The primary cilium is a dynamic organelle formed in a multistep process termed ciliogenesis that is tightly coordinated with the cell cycle. Genetic alterations, such as ciliary gene mutations, and epigenetic alterations, such as post-translational modifications and RNA processing of cilia related factors, give rise to human neurodevelopmental disorders and brain tumors such as Glioblastoma and Medulloblastoma. This review discusses the important role of genetics and epigenetics in primary cilia function during brain development and cancer formation. We summarize mouse and human studies of ciliogenesis and primary cilia activity in the brain, and detail how cilia maintain neuronal progenitor populations and coordinate neuronal differentiation during development, as well as how cilia control different signalling pathways such as Wnt, Shh and PDGF that are critical for neurogenesis. Moreover, we describe how post-translational modifications alter cilia formation and activity during development and carcinogenesis, and the impact of missplicing of ciliary genes leading to ciliopathies and cell cycle alterations. Finally, cilia genetic and epigenetic studies bring to light cellular and molecular mechanisms that underlie neurodevelopmental disorders and brain tumors.